1025 THE IMPACT OF DEPRIVATION AND FRAILTY ON THE LIKELIHOOD OF RECEIVING HIP AND KNEE ARTHROPLASTY DUE TO OSTEOARTHRITIS. (14th June 2022) - Cook, M J; Lunt, M; Board, T; O'Neill, T W
Abstract: Introduction: We determined the impact of deprivation and frailty at the time of diagnosis of hip or knee osteoarthritis (OA) on the likelihood of receiving total hip/knee arthroplasty (THA/TKA). Method: We used routinely collected primary care data (Clinical Practice Research Datalink), linked to Hospital Episode Statistics. Frailty was assessed at the time of OA diagnosis using the electronic frailty index and categorised as fit, mild, moderate, and severe frailty. The association between quintile of index of multiple deprivation (IMD), frailty category and likelihood of receiving THA and TKA was assessed in separate Cox regression models, adjusted for year of OA diagnosis, age, and sex. Results: 104, 672 individuals with hip OA and 220, 714 with knee OA contributed data. Compared to those in the first quintile of IMD (least deprived), those in the fourth and fifth quintile of IMD (most deprived), respectively, were less likely to receive THA, hazard ratio (HR) (95% CI), 0.92 (0.89, 0.95) and 0.80 (0.77, 0.83), with similar results for TKA. Increasing frailty at OA diagnosis was associated with reduced likelihood of receiving THA/TKA. Compared to fit individuals, the HR (95% CI) for receiving THA and TKA, respectively among those with severe frailty was 0.42 (0.39, 0.45) and 0.57 (0.53, 0.61). Increasing deprivation was associated with increasing frailty at the time of hip/knee OA diagnosis, independent of age, sex, and year of OA diagnosis. However, those in the two most deprived quintiles were still less likely to receive THA/TKA after additionally adjusting for frailty category. Conclusion: Increased deprivation and increased frailty category were associated with a lower likelihood of receiving THA/TKA among people with hip/knee OA. Increased frailty did not, however, explain the reduced likelihood of receiving THA/TKA among those living in the most deprived areas.